Rumen fermentation and nutrient utilization of growing Yankasa rams fed a mixed ration containing tiger nut (Cyperus esculentus) residue and cowpea husk (Vigna unguiculata L. Walp) - Yakubu, Hosea; Njidda, Ahmed Amin; Butswat, Isaac Sammani; Olafadehan, Olurotimi Ayobami; Bankole, Abayomi Samuel (Brazilian Journal of Science, 2024)
Thirty (30) Yankasa growing rams were used to investigate the effect of feeding cowpea husk and tiger nut residue in a mixed ration on the rumen ecology, nutrient intake, nutrient digestibility, and nitrogen balance of Yankasa rams. Significant differences (p < 0.05) were observed in the rumen ecology, nutrient intake, nutrient digestibility, and nitrogen balance between the treatments. Rumen ecology was influenced by the diet, with variations in rumen pH, temperature, and volatile fatty acid production. The results indicated that the highest rumen pH and temperature were observed in Treatment 2, while acetate, butyrate, and propionate levels varied among treatments. Nutrient intake and digestibility were significantly affected by the diet. Dry matter intake, crude protein intake, nitrogen detergent fiber (NDF), and acid detergent fiber (ADF) intake varied among treatments. Treatment 3 showed the highest dry matter intake, while Treatment 5 had the highest NDF intake. Crude protein intake was highest in Treatment 3, and the highest values for most nutrients were observed from the same treatment. The results for nitrogen balance in Yankasa rams indicate a positive nitrogen balance, suggesting that the rams received adequate amounts of nitrogen from the diets fed. Feeding 20% cowpea husk and 20% tiger nut residue provides optimum performance for rams in terms of rumen fermentation, and nutrient utilisation.